2013
DOI: 10.1099/ijs.0.034280-0
|View full text |Cite
|
Sign up to set email alerts
|

Bradyrhizobium daqingense sp. nov., isolated from soybean nodules

Abstract: Thirteen slow-growing rhizobial strains isolated from root nodules of soybean (Glycine max L.) grown in Daqing city in China were classified in the genus Bradyrhizobium based on 16S rRNA gene sequence analysis. Multilocus sequence analysis of IGS, atpD, glnII and recA genes revealed that the isolates represented a novel clade in this genus. DNA-DNA relatedness lower than 42.5 % between the representative strain CCBAU 15774 T and the type strains of the closely related species Bradyrhizobium liaoningense USDA 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 68 publications
(92 reference statements)
3
28
1
1
Order By: Relevance
“…The 272 Bradyrhizobium strains used in this study (see Table S1 and Fig. S1 in the supplemental material) were previously collected from soybean nodules in four ecoregions of China (South China, Huanghuaihai, Northeast China, and Xinjiang) (2,3,6,8,10,33). These strains were grown in TY medium at 28°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 272 Bradyrhizobium strains used in this study (see Table S1 and Fig. S1 in the supplemental material) were previously collected from soybean nodules in four ecoregions of China (South China, Huanghuaihai, Northeast China, and Xinjiang) (2,3,6,8,10,33). These strains were grown in TY medium at 28°C.…”
Section: Methodsmentioning
confidence: 99%
“…It has been recurrently reported that Bradyrhizobium japonicum, Bradyrhizobium elkanii, Bradyrhizobium liaoningense, Bradyrhizobium yuanmingense, and Sinorhizobium fredii could nodulate soybeans (2)(3)(4)(5). Recently, Bradyrhizobium huanghuaihaiense, Bradyrhizobium daqingense, Sinorhizobium sojae, and several unnamed species were also found to be effective microsymbionts of soybeans (2,3,(6)(7)(8). Strain USDA110 represents a widely distributed type formerly known as B. japonicum Ia, but it has recently been proposed as a member of the new species Bradyrhizobium diazoefficiens (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Concordantly, the Namibian bradyrhizobia were phylogenetically and physiologically more diverse, with the bulk being related to B. yuanmingense and B. daqingense. While B. daqingense was described just recently (58) and information is limited, B. yuanmingense seems to be widespread in the subtropics and tropics and was found, e.g., in China (59), India and Mexico (23), Peru (60), Botswana (61), and South Africa (10). Moreover, the Namibian isolates were very diverse even within the groups, as could be seen in the BOX-PCR fingerprinting.…”
Section: Pachyrhizimentioning
confidence: 97%
“…Rhizobiaare highly diverse and classified into several genera and species. The slow-growing, soybean-nodulating rhizobia are B. japonicum (Jordan, 1982), B. elkanii (Kuykendall et al, 1992), B. liaoningense (Xu et al, 1995), B. huanghuaihaiense (Zhang et al, 2012), B. daqingense (Wang et al, 2013), B. diazoefficiens (Delamuta et al, 2013) and B. ottawaense (Yu et al, 2014). The fast-growing bradyrhizobia are classified into twoSinorhizobium (Ensifer) species: S. fredii (Chen et al, 1998)and S. soyae (Li et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%